Analisis Butir Soal Matematika pada Instrumen Pretest/Postest Topik Trigonometri - Khairiati Khairiati (Anotero Lembaga Scientific Pekanbaru, 2022)
This study aims to determine the quality of mathematical items on the topic of Trigonometry. The items are pretest/posttest questions that have been tested on class XI students who have studied the topic of Trigonometry. The research method used is descriptive quantitative method. The data collection technique used the statistical application of the Anates 4.05 program. Based on the data analysis, it was found that the validity of the questions was categorized as good and very good. In addition, the test reliability value was obtained with 0.79 points which stated that the question had a very high level of reliability. Based on the differentiating power, the items are quite good and are classified as easy and medium questions based on the level of difficulty. The quality of the pretest/posttest items is valid and reliable and deserves to be tested.